Practices, beliefs and attitudes about complementary feeding among turkish mothers: a qualitative study - Doğan, Satı; Sert, Zuhal Emlek; Topçu, Sevcan (Progress in Nutrition, 2019)
In this research the experiences, viewpoints and attitudes of mothers who have babies between 6 to 24 months old, related to transition to complementary feeding are explained. A qualitative investigation design was used. Research was carried out in 7 Family Health Centers (FHC) located in town of Ödemiş. Twenty mothers who had babies between 6 to 24-year old agreed to participate in the study. The experiences, viewpoints and attitudes of mothers having babies between 6 to 24-month old related to complementary feeding were analyzed in line with their knowledge, experiences, resources and cultural themes related to complementary feeding. Fourteen of mothers (70%) stated that they did not exactly know the right starting time of complementary feeding. Seven mothers (35%) reported that they had experiences babies’ health problems such as constipation, growth-development failure, etc. after starting complementary feeding. Mothers’ knowledge level about complementary feeding isn’t enough. Primiparous mothers generally are to learn complementary feeding from their environment instead of health worker. Mothers should be encouraged to explain complementary feeding practices. Wrong practices should be corrected by health workers.